Mapping out internal audit research: a bibliometric analysis - Zhang, Chi; Mohammed Shah, Sabarina; Lau, Yeng Wai; Ngalim, Siti Manisah (David Publishing Company, 2024)
This paper aims to map out the development of internal audit (IA) research worldwide by using a bibliometric analysis method to statistic the publications in the Scopus database. There are new challenges, especially during the COVID-19 pandemic, bringing out remote auditing with new technologies; hence there are new risks that must be addressed. The bibliometric analysis was carried out from 1978 until September 2024. And this research used the VOSviewer visualisation technique to present co-relations with authorship, countries, and affiliations to show a research network base on the data sources, the Scopus database. This study’s findings show that internal audit research publications were growing steadily within 15 years, and most publications are from the United States, Malaysia, and the United Kingdom. With analyses of the author’s keywords, China becomes the focus research nation on IA research from 2019 to 2024, and in the recent five years, IA research has developed fast. The IA is essential in corporate governance and internal control and provides assurance and consultant functions to prevent fraud and reduce risk. Also, visualising keywords, titles, and publication abstracts leads to discovering new research areas, such as the relationship between internal audit and fraud, risk assessment and corporate governance, respectively. This study builds a macroscopic pattern and a better network to understand global internal auditing research. In addition, it performs network analysis on keywords and titles, which leads to the development of the cluster field, and maps the authorship, sources, and citations.